Surgical treatment of war posttraumatic pleural empyemas - Cvijanović Vlado; Stanić Vojkan; Ristanović Aleksandar; Gulić Bojan; Kovačević Snežana (Vojnosanitetski Pregled)
Background/Aim. Posttraumatic pleural empyema is the most frequent septic complication of the thoracic penetrating war injuries. Surgical treatment used to be based on the experience gained in the treatment of parapneumonic empyema, the most frequent empyema, and used to be favored the pleural drainage until the nineties of the last century. Thoracotomy and decortication was performed in case of drainage failure, in early chronic phase, 4-6 weeks after injury. The aim of this study was to emphasize the necessity of different surgical approaches in the treatment of this disease which is based on the different pathophisyology of posttraumatic and other sorts of empyema. Also, to recommend on the basis of the surgical treatment results, early decortication as better method in the treatment of this septic complication. Methods. In the period between September 1991-June 1999. 1 303 thoracic injures were surgically treated. There were 1 117 penetrating injures with 675 dominant thoracic injures, and 442 thoracic injures as the following ones. In 59 (5.3%) injured people raised posttraumatic empyema (PET). The patients were divided into the groups with early and late decortications regarding the interval between the injury and the surgical treatment. Almost all the patients sustained this complication in various periods before the admittance to the hospital. Surgical treatment efficiency of early and late decortication was analyzed on the basis of perioperative and postoperative study parameters and analyzing postoperative complications. Results. Thoracotomy and decortication were performed in 46 (78%) injured patients with post traumatic pleural empyema while only 13 (22%) injured patients were successfully treated for this septic complication with drainage procedures. This study proved that there were in the group with early decortications lesser intra and postoperative blood loss, duration of operation was shorter as well as febrile postoperative period. In this group, also, hospitalization was shorter and with lesser complications. Conclusion. The obtained results showed that thoracotomy and decortication should be done as early as possible in patients, not later than two weeks after the injury.